STATISTICALLY OPTIMIZED GROWTH CONDITIONS OF LACTOBACILLUS PARACASEIKUMBB005 FOR ENHANCED Β-GALACTOSIDASE PRODUCTION - V. USHA RANI; B.V. PRADEEP (International Journal of Pharma and Bio Sciences, 2016)
Lactobacillus paracasei KUMBB005 has been studied for β-galactosidase production. The culture parameters were statistically optimized using Response Surface Methodology. The five factors such as pH, temperature, incubation time, glucose and lactose concentration were evaluated by Box-Behnken design. Based on the ANOVA test the effect of interactions were significant with R2 = 0.091 at 1% level (p<0.0001). The optimum conditions for enzyme production were obtained as pH 6, temperature 37 ºC, 24 h incubation, 2% glucose and 5 % lactose concentration, with production yield of 105.00U/mL β galactosidase.